MAGNITUDE DRIFT EFFECT WINNER AND LOSER STOCKS: LQ45 AND FTSE100 - Felita Tanuprasodjo; Putu Anom Mahadwartha (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2016)
This research is aimed to examine and find out empirical evidence of magnitude drift effect on 10 winner LQ45, 10 loser LQ45, 5 winner FTSE100 Malaysia and 5 loser FTSE100 Malaysia. One sample t-test and independent sample t-test are used to test the magnitude drift effect. The result show the positive magnitude drift effect on Monday-Wednesday at 10 Winner LQ45 and 5 winner FTSE100, Monday-Tuesday at 10 Loser LQ45, Monday-Thursday at 5 Loser FTSE100 and the negative magnitude drift effect occurs on Thursday-Friday at 10 Winner LQ45 and 5 Loser FTSE100, Wednesday-Friday at 10 Loser LQ45 and Friday-Monday at 5 Winner FTSE100. Magnitude drift in Malaysia occurs more than magnitude drift in Indonesia.